Residual dizziness after successful canalith repositioning: impact on cognitive function and dual-task performance in BPPV patients. - Gurel Soylemez, Tugce; Söylemez, Emre; Yiğit, Öznur (Journal of Laryngology & Otology, 2026)
Objectives: This study investigated the impact of residual dizziness after successful canalith repositioning manoeuvre on cognitive functions and dual-task performance in patients with benign paroxysmal positional vertigo (BPPV). Methods: Forty-four patients with posterior canal BPPV were assessed 1 week after successful treatment and divided into 2 groups: with residual dizziness (n = 22) and without residual dizziness (n = 22). Cognitive function was evaluated using the Stroop test and digit span test. Dual-task performance was assessed with a combination of the timed up and go test and the digit span test. Results: Residual dizziness was associated with longer BPPV duration, and higher anxiety and disability levels (p < 0.05). Patients with residual dizziness performed worse on the Stroop test (p < 0.05), while no significant differences were found in digit span or dual-task performance (p > 0.05). Conclusion: The results highlight a dynamic interplay between cognitive and vestibular systems. Residual dizziness may impair cognitive performance, while baseline cognitive deficits may also increase vulnerability to residual dizziness.